Service-learning in first-year composition: using critical reflection to ensure student learning and benefit to the community partner - Calvert, Chandra, author; Langstraat, Lisa, advisor; Doe, Sue, committee member; Greene, David, committee member (Colorado State University. Libraries, 2015)
Over the past few decades, service-learning has taken hold in English departments at colleges and universities across the U.S, as service-learning offers real-world rhetorical situations for composition students. Further, some composition instructors have created first-year composition courses that include service-learning and it helps to connect incoming students with their communities, which has been found to be a means to improving retention from the first year of college to the second. This thesis sets forth the claim that service-learning is a viable option for first-year composition courses, but must follow certain parameters if the course is to be of benefit to both students taking the course and the community partner. A focus on reciprocity is key, including involving the community partner early in the planning of the course so they have a say in the structure of the service-learning portion of the course. Secondly, while reflection has long been seen as a vital component of any service-learning course, composition courses should go a step further to require critical reflection so students can confront their own struggles early on, increasing the likelihood of a successful, positive outcome for both the student and the community partner. What follows is a brief history of service-learning in first-year composition courses as well as a review of literature the sub-topics included in the claim (needs of first year students, the importance of reciprocity, and critical reflection to name a few) as well as suggestions on how to incorporate critical reflection into a first-year service-learning composition course that is of mutual benefit to both the student and the community partner.